The Impact of Free Meal Programs in the Education Curriculum on the Formation of Healthy Eating Patterns and the Preservation of Local Culture in East Lombok - Supnawadi, Supnawadi; Suprapto, Suprapto; Khusniyah, Nurul Lailatul; Thoib , Ismail (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
Child nutrition issues during school age are a strategic concern in human resource development. Most studies on school feeding programs focus on improving nutrition, while cultural dimensions are rarely examined. This study is academically significant as it highlights the dual role of school-based interventions: improving healthy eating patterns while strengthening cultural identity through the integration of local cuisine. This study aims to analyze the impact of a free school meal program based on local cuisine on the formation of healthy eating habits and cultural preservation among elementary and secondary school students in East Lombok. A quantitative approach with a quasi-experimental design using a non-equivalent control group was employed. A total of 100 students were purposively selected, with 50 from urban schools and 50 from rural schools. Data were collected through questionnaires, observations, and brief interviews, validated by experts in nutrition, education, and culture, and tested for reliability using Cronbach’s Alpha with a value exceeding 0.70. Analysis was conducted using paired t-tests and two-way ANOVA after assumptions of normality and homogeneity were met. The results showed a significant improvement in healthy eating scores in the experimental group compared to the control group (p < 0.01). Additionally, over 70% of students in the experimental group demonstrated improved understanding and appreciation of local cuisine, while improvements in the control group were relatively low. These findings confirm that integrating traditional foods into free school meal programs is not only effective in improving health but also contributes to cultural education. This study has practical implications for policymakers and educators in designing school nutrition programs that also serve as a means of preserving local identity.